Genetic characterization of porcine reproductive and respiratory syndrome virus from Eastern China during 2017–2022 - Zhou, Lujia; Yang, Yang; Xia, Qiqi; Guan, Zhixin; Zhang, Junjie; Li, Beibei; Qiu, Yafeng; Liu, Ke; Shao, Donghua; Ma, Zhiyong; Wang, Xiaodu; Wei, Jianchao (Frontiers in Microbiology, 2022)
Porcine reproductive and respiratory syndrome (PRRS) is an immunosuppressive disease caused by PRSS virus (PRRSV). Classical strains mainly cause reproductive disorders in pregnant sows and respiratory diseases in piglets. Highly pathogenic mutant strains cause acute febrile and highly fatal diseases, which are infectious. At present, new PRRSV mutants continue to appear. PRRS has become one of the most important diseases in the pig industry in China and even the world. We collected clinical samples from differently sized pig farms in Eastern China from 2017 to 2022 to analyze the epidemic characteristics of the disease. We obtained 13 PRRSV-positive samples. Phylogenetic analysis based on the ORF5 sequence revealed that all 13 strains belonged to type 2, and they were mainly distributed in four lineages. We found two NADC34-like strains in Jiangsu Province, indicating that these strains were evident in this region. The major structural protein glycoprotein (GP5) protein is encoded by ORF5. R13 and R151 of the GP5 protein are related to the pathogenicity of the virus. Analysis of deduced amino acid mutation sites revealed that 5 out of 13 strains showed mutations of R13 and 4 out of 13 strains showed mutations of R151. Epitope analysis of the 13 isolated strains and additional reference strains revealed that all 13 strains had some mutations on the decoy epitope, the primary neutralizing epitope, T cell epitopes, and B cell epitopes. N-linked glycosylation site (NGS) analysis revealed that 6 of 13 strains had varying degrees of deletion and addition at the NGSs. Deletions, mutations, and additions in the NGSs of these strains may enhance the resistance of PRRSV to neutralizing antibodies and lead to vaccine failure. This study further enriches the epidemiological data of PRRS in Eastern China and provides a theoretical basis for vaccine development and prevention and control of the disease.